Impact of fluctuating actinic high light stress on biomass and yield of cassava - Sadasivan Nair Raji; Saravanan Raju; Velumani Ravi (JOURNAL OF ROOT CROPS, 2023)
Cassava (Manihot esculenta Crantz) is a staple crop grown in the tropics for food as a major calorie source as well as in industrial use. In natural environment, crops undergo rapidly changing light conditions which affects the photosynthetic efficiency. When exposed to excess photon flux densities, plants under go non photochemical quenching (NPQ) by which the excess energy is harmlessly dissipated as heat in order to protect the plants from photo-damage. Upon the transition to low or optimal light for photosynthesis, the slow rate of recovery of NPQ can limit effective photosynthetic efficiency which consequently results in low crop productivity. In the present study, the physiological and fluorescence responses of six field grown cassava genotypes to intermittent high red actinic light (IHL) were examined and compared against control plants grew under ambient light conditions. From the results, it was seen that overall average values of plant height and fresh above ground biomass (ABM) was higher under IHL conditions (206.6±26.5 cm and 2.34±0.67 Kg respectively), while high crop biomass (CBM) was observed in control condition (3.11±0.86 Kg). It was found that Sree Suvarna had the maximum CBM under both the control and IHL conditions (4.31±0.32 Kg and 4.11±0.44 Kg respectively). Higher average values of Pn measured was 34.04±1.6 ?molm-2s-1 (Control - Sree Suvarna), NPQ was 2.12±0.36 (IHL - Sree Athulya) and qN was 0.85±0.03 (Control - Sree Pavithra). Significant difference in fluorescence parameters and crop yield were observed between the light conditions and also between the cassava varieties. It was inferred that IHL has obviously affected the NPQ induction/relaxation process which resulted in reduced CBM compared to that under control condition.